2005
DOI: 10.1016/j.ijheatmasstransfer.2004.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of heat transfer in rectangular microchannels

Abstract: An experimental investigation was conducted to explore the validity of classical correlations based on conventional-sized channels for predicting the thermal behavior in single-phase flow through rectangular microchannels. The microchannels considered ranged in width from 194 m to 534 m, with the channel depth being nominally five times the width in each case. Each test piece was made of copper and contained ten microchannels in parallel. The experiments were conducted with deionized water, with the Reynolds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
313
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 716 publications
(333 citation statements)
references
References 28 publications
17
313
3
Order By: Relevance
“…From graph 5.1, it is observed that for higher flow rates experimental value is closer to the theoretical results and compared with the graph of P. S. Lee et al [5] which is draw by using correlation given in journal paper. The heat transfer losses to the surrounding atmosphere due to radiation and conduction losses through acrylic are not taken into account for calculation of the theoretical heat transfer coefficient.…”
Section: Discussion Of Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…From graph 5.1, it is observed that for higher flow rates experimental value is closer to the theoretical results and compared with the graph of P. S. Lee et al [5] which is draw by using correlation given in journal paper. The heat transfer losses to the surrounding atmosphere due to radiation and conduction losses through acrylic are not taken into account for calculation of the theoretical heat transfer coefficient.…”
Section: Discussion Of Resultssupporting
confidence: 76%
“…Hence, there is deviation observed between theoretical and experimental value. From graph 5.3, it is observed that thermal resistance deceased with the increase in Reynolds number for experimental, theoretical and P. S. Lee et al [5] graph which is drawn by correlation given in journal paper, also experimental value is more than that of theoretical. This is happen due to heat supplied to the microchannel increases and temperature difference of water between inlet and outlet of microchannel is decreased, hence according to Fourier law of conduction and Newton's law of cooling the thermal resistance is decreased as Reynolds number increases.…”
Section: Discussion Of Resultsmentioning
confidence: 76%
See 3 more Smart Citations